Recipient Hyperbilirubinemia May Reduce Ischemia-Reperfusion Injury but Fails to Improve Outcome in Clinical Liver Transplantation - Mihai Oltean; Christian Barrenäs; Paulo Ney Martins; Gustaf Herlenius; Bengt Gustafsson; Styrbjörn Friman; William Bennet (Gastroenterology Research and Practice)
Background. Exogenous bilirubin may reduce experimental ischemia-reperfusion injury (IRI) due to its antioxidant properties. We studied if early graft exposure to high bilirubin levels in the recipient affects the early IRI and outcomes after liver transplantation (LTx). Methods. In 427 LTx patients, the AUROC curve based on bilirubin and AST at day 1 identified a cutoff of 2.04 mg/dL for the recipient pretransplant bilirubin. Recipients were grouped as having low (group L, n=152) or high (group H, n=275) bilirubin. Both groups had similar donor-related variables (age, preservation time, donor BMI > 28, and donor risk index (DRI)). Results. Alanine (ALT) and aspartate (AST) aminotransferase levels were higher in group L at day 1; ALT levels remained higher at day 2 in group L. LTx from high risk donors (DRI > 2) revealed a trend towards lower transaminases during the first two days after transplantation in group H. One month and 1-year patient survival were similar in groups L and H. High preoperative bilirubin did not affect the risk for early graft dysfunction (EGD), death, or graft loss during the first year after transplantation nor the incidence of acute rejection. LTx using donors with DRI > 2 resulted in similar rates of EGD in both groups. Conclusion. Increased bilirubin appears to reduce the early IRI after LTx yet this improvement was insufficient to improve the clinical outcome.